2019
DOI: 10.1111/brv.12544
|View full text |Cite
|
Sign up to set email alerts
|

Fire as a key driver of Earth's biodiversity

Abstract: Many terrestrial ecosystems are fire prone, such that their composition and structure are largely due to their fire regime. Regions subject to regular fire have exceptionally high levels of species richness and endemism, and fire has been proposed as a major driver of their diversity, within the context of climate, resource availability and environmental heterogeneity. However, current fire-management practices rarely take into account the ecological and evolutionary roles of fire in maintaining biodiversity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
267
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(325 citation statements)
references
References 266 publications
(342 reference statements)
10
267
1
10
Order By: Relevance
“…For example, Leahy et al (2016) found an initial increase in dingo detections 2 weeks after a high severity fire, but because we calculated pooled mean abundances in burnt and unburnt areas across the whole sampling period, the short-term response was not clearly captured in the effect size calculation. The lack of predator responses to fire was unexpected given the broad potential effects of fire on ecosystems (Bond & Keeley, 2005;He et al, 2019). Many predators, especially mammals and birds, use a wide variety of habitats due to their large home ranges and generalist diets (Santos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Leahy et al (2016) found an initial increase in dingo detections 2 weeks after a high severity fire, but because we calculated pooled mean abundances in burnt and unburnt areas across the whole sampling period, the short-term response was not clearly captured in the effect size calculation. The lack of predator responses to fire was unexpected given the broad potential effects of fire on ecosystems (Bond & Keeley, 2005;He et al, 2019). Many predators, especially mammals and birds, use a wide variety of habitats due to their large home ranges and generalist diets (Santos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fire has shaped Earth's ecosystems for millennia through the combustion of vegetation (Bond & Keeley, 2005), influencing how animals such as predators behave and are distributed in fire-prone landscapes (He, Lamont, & Pausas, 2019;Hradsky, Mildwaters, Ritchie, Christie, & Stefano, 2017). In their native ranges, apex predators can have positive effects on ecosystems and biodiversity by limiting the activity or abundance of herbivores and smaller 'mesopredators', either through killing (Pasanen-Mortensen, Pyykönen, & Elmhagen, 2013) and/or by instilling fear (Swanson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fire ecologists have constructed an increasingly nuanced, sophisticated and mechanistic understanding of the variable nature of fire as part of the ecological system. Fire is now recognized as a recurrent process, resulting in fire regimes that have direct ecological effects and act as selective forces by shaping species traits throughout the histories of entire lineages (He, Lamont, & Pausas, 2019; Simon et al., 2009). Moreover, fire regimes are important at multiple levels of biological organization, influencing populations, communities and ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Wildfire management is an escalating issue globally, with economic, environmental, social and cultural consequences [1][2][3][4]. In fire-prone regions such as the Americas, Australia and parts of Asia and Africa, wildfire management presents a formidable ongoing challenge that must be urgently addressed.…”
Section: Introductionmentioning
confidence: 99%